Mycobacterium abscessus DosRS two-component system controls a species-specific regulon required for adaptation to hypoxia - Simcox, Breven S.; Tomlinson, Brooke R.; Shaw, Lindsey N.; Rohde, Kyle H. (Frontiers in Cellular and Infection Microbiology, 2023)
Mycobacterium abscessus (Mab), an emerging opportunistic pathogen, predominantly infects individuals with underlying pulmonary diseases such as cystic fibrosis (CF). Current treatment outcomes for Mab infections are poor due to Mab’s inherent antibiotic resistance and unique host interactions that promote phenotypic tolerance and hinder drug access. The hypoxic, mucus-laden airways in the CF lung and antimicrobial phagosome within macrophages represent hostile niches Mab must overcome via alterations in gene expression for survival. Regulatory mechanisms important for the adaptation and long-term persistence of Mab within the host are poorly understood, warranting further genetic and transcriptomics study of this emerging pathogen. DosRSMab, a two-component signaling system (TCS), is one proposed mechanism utilized to subvert host defenses and counteract environmental stress such as hypoxia. The homologous TCS of Mycobacterium tuberculosis (Mtb), DosRSMtb, is known to induce a 50 gene regulon in response to hypoxia, carbon monoxide (CO) and nitric oxide (NO) in vitro and in vivo. Previously, a small DosRMab regulon was predicted using bioinformatics based on DosRMtb motifs however, the role and regulon of DosRSMab in Mab pathogenesis have yet to be characterized in depth. To address this knowledge gap, our lab generated a Mab dosRS knockout strain (MabΔdosRS) to investigate differential gene expression, and phenotype in an in vitro hypoxia model of dormancy. qRT-PCR and lux reporter assays demonstrate Mab_dosR and 6 predicted downstream genes are induced in hypoxia. In addition, RNAseq revealed induction of a much larger hypoxia response comprised of >1000 genes, including 127 differentially expressed genes in a dosRS mutant strain. Deletion of DosRSMab led to attenuated growth under low oxygen conditions, a shift in morphotype from smooth to rough, and down-regulation of 216 genes. This study provides the first look at the global transcriptomic response of Mab to low oxygen conditions encountered in the airways of CF patients and within macrophage phagosomes. Our data also demonstrate the importance of DosRSMab for adaptation of Mab to hypoxia, highlighting a distinct regulon (compared to Mtb) that is significantly larger than previously described, including both genes conserved across mycobacteria as well as Mab-specific genes.